Desempeño Laboral en el Gad Parroquial Rural de la Victoria -Salitre -Guayas - Palma Aguirre, Carmen Elizabeth (2018)
The Autonomous Decentralized Parochial Rural Government The Victory, Located in the street Av. Enrique Décker, in front of the Mixed National School "The Victory" pertaining to the Canton Salitre Province of the Guayas. Institution dedicated to the progress of the parish and rural sectors consists of nine people including a President, four members, a secretary, a treasurer, an assistant, and a person of administrative cleaning. The